Teaching English articles to Ilokanos - Salcedo, Phoebe Luz (Blanco) 1928- ([Quezon City s.n.], 1966)
In the Philippines, the studies of Dizon, Arevalo and Songco, of Caridad, and of Trinidad on the types of errors in English committed by elementary pupils; of Phoebe Salcedo on the types of article-errors in English of Freshman students in 1962; and her just-completed survey of elementary and secondary school textbooks in English from 1920 to 1965 show that there is a need to teach English articles to Filipinos better than they were taught in the past.
Thesis (M.A.T.)--University of the Philippines
Keywords: Iloko language -- Article; English language -- Article